Dialect Levelling: A Case Study of Ìkàr??-Àkókó Dialect - Bamigbola, Esther Olayinka; Umar, Fadekemi Rukayat (International Journal of Language and Literary Studies, 2021)
This study investigates the factors that are responsible for the levelling of Ìkàr??-Àkókó dialect. Specifically, the paper examines the impacts of Nigerian indigenous languages, especially Yorùbá, on the dialect. The study aims at identifying the patterns of changes in the dialect and their impacts on the ethnic identities of the people. The work is based on the variationist approach pioneered by William Labov in the late 1960s and early 1970s. The tools used for data collection include questionnaire, oral interview and observation. The findings of the study reveal that the dialect manifests different stages of changes, vital domains like home, school and work place, which are supposed to be the strongholds of this dialect are being encroached upon by languages other than the mother tongue in the study area. It was found that the changes in the dialect are not due to the influence of English language only, but to indigenous Nigerian languages, mostly Yorùbá. It was concluded that the gradual levelling of Ìkàr??-Àkókó dialect is caused in part by restricted domains of use, increase in population; lack of commitment to indigenous language use by the native speakers; and suppressive language policy in the nation. The study recommends sensitization campaigns as a way of maintaining and sustaining the status of indigenous languages.